The Effectiveness of Alphabet an The Effectiveness of Alphabet and Picture Box Learning Media (KOFABAR) to Improve Beginning Reading Skills for Children with Cerebral Palsy - Nisa, Rahmatun; Nurhastuti, Nurhastuti; Zulmiyetri, Zulmiyetri; Taufan, Johandri; Tsaputra, Antoni (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this study was to examine the effectiveness of kofabar learning media to improve the ability of beginning reading for children with cerebral palsy. The approach used in this research is SSR with A-B-A design. The study was conducted over 14 sessions, divided into three phases, the first phase, baseline (A1), was conducted for 3 meetings, showing stable results with a score of 7%. The second phase, namely intervention (B), was carried out for 8 meetings, showing an increase with a score of 13% to 93% and showed stability at the 6th meeting to the 8th meeting. The last phase, namely baseline (A2), was conducted for 3 meetings, showing stable results with a score of 86%. These results indicate an increase in the ability to read beginning using kofabar learning media for cerebral palsy children.